Mathematics 2010 | Study Mode

Join Discuss Share Question Share to WhatsApp
Question 1
A
1/3 
B
C
D
1/6 
Explanation.
Share Answer \(\left(\frac{81}{16}\right)^{\frac{-1}{4}}\times 2^{-1}=\frac{1}{\left(\frac{81}{16}\right)^{\frac{1}{4}}}\times \frac{1}{2}\\
=\left(\frac{16}{81}\right)^{\frac{1}{4}}\times \frac{1}{2}\\
=\left(\frac{2}{3}\right)^{4\times \frac{1}{4}}\\
=\frac{2}{3}\times \frac{1}{2}\\
=\frac{1}{3}\)

Correct Option:
A
Join Discuss Share Question Share to WhatsApp
Question 3
A
10 
B
C
15 
D
20 
Explanation.
Share Answer Let C n G = X
n C only = 40 - x
n G only = 30 - x
40 - X + 30 - X = 50
70 - X = 50
X = 70 - 50
X = 20Maths-explained-image

Correct Option:
D
Join Discuss Share Question Share to WhatsApp
Question 6
A
q = 18 
B
p <1 
C
p = 18 
D
q < 1 
Explanation.
Share Answer Using substitution If 18(p+18) = (18 + p)q
let q = 18
imply 18(p+18) = (18+p)18
i.e 18p + 18 x 18 = 18 x 18 + 18p
Since the left hand side = the right hand side
imply that q = 18

Correct Option:
A
Join Discuss Share Question Share to WhatsApp
Question 9
A
B
C
D
Explanation.
Share Answer \(\left[\begin{array}{cc}
x & 3\\
2 & 7\end{array}\right]\)= 15
x x 7 - 2 x 3 = 15
7x - 6 = 15
7x = 15+6
7x = 21
x = 21/7
x = 3

Correct Option:
A
Next Page
Question Map
Quiz link
Share Mathematics 2010 with your friends
Share to WhatsApp Share Quiz CBT mode Study mode copy link